A QUALITATIVE EXPLORATORY ANALYSIS OF THE IMPACT OF PERCEIVED EROSION OF THE POLITICSADMINISTRATION DICHOTOMY ON GOOD GOVERNANCE AND SERVICE DELIVERY IN A DEMOCRATIC DEVELOPMENTAL STATE: SOUTH AFRICAN PERSPECTIVE - Bogopane, LP (European Scientific Journal, ESJ, 2014)
This article provided a qualitative exploratory analysis on the impact of perceived erosion of the politics-administration dichotomy on good governance and service delivery in a democratic developmental state within the context of South Africa. It began by providing an introductory background as well as a theoretical perspective on the phenomenon of ‘politics-administration dichotomy’ and highlighted on the significant role that this phenomenon plays in promoting democratic public bureaucracy and good governance. The manuscript identified four themes which are said to be fundamental to functional and wellperforming politics-administration dichotomy relations, namely: (a) strong and visionary political leadership; (b) vibrant apolitical public bureaucracy: (c) well-coordinated and integrated political and administrative structures and systems; and (d) well-mobilised citizenry for active participation, and used them as a basis for this exploratory analysis. Qualitative data collection methods (such as participant observation; in-depth interviewing; qualitative document study; and qualitative case study) and data analysis and interpretation techniques such as qualitative content analysis and qualitative case analysis) were used in this study. Based on the research objectives pertinent to this study, several findings were arrive at, and on their basis, a (a) Strong visionary political and administrative leadership; (b) vibrant apolitical strong public bureaucracy; (c) well-coordinated and integrated political and administrative structures and systems; and (d) well-mobilised active participatory citizenry politics-administrative model, was proposed and recommended with the belief that if, and only if it can be properly adopted and implemented, could lead to the improvement to the functionality and performance of politics-administration dichotomy relations in Mzansi.